IMPLEMENTASI KEBIJAKAN GERAKAN PENERAPAN PENGELOLAAN TANAMAN TERPADU JAGUNG DI KECAMATAN TIKKE RAYA KABUPATEN MAMUJU UTARA - Alwi, Muhammad (Katalogis, 2018)
This study aimed to determine the implementation of Corn Integrated Crop Management Application Movement Policy in Tikke Raya District, North Mamuju Regency, West Sulawesi Province. The author used the theory of Edward III to determine the factors influencing the implementation of the policy, such as the factors of communication, resources, disposition, and bureaucratic structure. This study used qualitative research, with descriptive method. Based on the results, it was concluded that Implementation of Corn Integrated Crop Management Application Movement Policy in Tikke Raya District North Mamuju Regency had been running well, this was evidenced by the theoretical approach of Edward III by looking at four (4) indicators, namely communication, resources, disposition, and bureaucratic structure. The communication aspect in this program ran well so that the whole implementers and target groups knew their tasks and responsibilities. The resources needed were adequate, the disposition of the parties involved was very supportive for the smooth implementation of the policy. The bureaucratic structure had been structured well and technical guidelines also ran well, but coordination between the implementing agencies was still needed to be improved